2012
DOI: 10.1021/jm300310c
|View full text |Cite
|
Sign up to set email alerts
|

Use of Small-Molecule Crystal Structures To Address Solubility in a Novel Series of G Protein Coupled Receptor 119 Agonists: Optimization of a Lead and in Vivo Evaluation

Abstract: G protein coupled receptor 119 (GPR119) is viewed as an attractive target for the treatment of type 2 diabetes and other elements of the metabolic syndrome. During a program toward discovering agonists of GPR119, we herein describe optimization of an initial lead compound, 2, into a development candidate, 42. A key challenge in this program of work was the insolubility of the lead compound. Small-molecule crystallography was utilized to understand the intermolecular interactions in the solid state and resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 45 publications
2
53
0
1
Order By: Relevance
“…G Protein-coupled receptor 119 agonists [16]. Disruption of intermolecular interaction between oxygen of the sulfonyl group and hydrogen of a methyl group in the agonist 5 was reported.…”
Section: Improvement Of Solubility By Disrupting Intermolecular mentioning
confidence: 99%
“…G Protein-coupled receptor 119 agonists [16]. Disruption of intermolecular interaction between oxygen of the sulfonyl group and hydrogen of a methyl group in the agonist 5 was reported.…”
Section: Improvement Of Solubility By Disrupting Intermolecular mentioning
confidence: 99%
“…For these reasons, the development of GPR119 agonists has attracted considerable interest as potential pharmacotherapies for type-2 diabetes and obesity (Cornall et al, 2013;Kang, 2013;Ohishi and Yoshida, 2012). A number of chemically diverse synthetic GPR119 agonists have been developed and characterized (Brocklehurst et al, 2011;Scott et al, 2012;Semple et al, 2008Semple et al, , 2011, with four having advanced to clinical trials (Ohishi and Yoshida, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study we have investigated the chronic effects of the endogenous GPR119 agonist oleoylethanolamide as well as the synthetic agonists AR-231,453, GSK-1292263, MBX-2982, AZ1, AZ2, and AZ3, as described previously (Brocklehurst et al, 2011;Scott et al, 2012;Semple et al, 2008) and shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with 12, the (R)-methyl offered no improvement in potency or metabolic stability when combined with either nitrile headgroup (29,30). However, dimethoxy compound 31 gave a small increase in potency and reached the limit of quantification for our standard HLM assay.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…We suggest that the introduction of a sulfone may have increased crystal packing, as recently reported for a series of GPR 119 agonists. 29 In addition, both 19 and 23 had markedly improved metabolic stability, with the result that when 23 was studied in vivo, bioavailability improved to 16% (rat in vivo Cl = 22 mL/min/ kg). As a result of these interesting observations, further analogues to investigate the SAR around the dimethoxy and sulfone moieties were studied.…”
Section: ■ Results and Discussionmentioning
confidence: 99%